Long-term budesonide treatment of collagenous colitis: a randomised, double-blind, placebo-controlled trial. Issue 1 (31st July 2008) - Bonderup, O K; Hansen, J B; Teglbjærg, P S; Christensen, L A; Fallingborg, J F
Abstract : Objective: To evaluate the efficacy and safety of long-term budesonide therapy for the maintenance of clinical remission in patients with collagenous colitis. Design: Randomised, placebo-controlled study with a 24-week, blinded follow-up period without any treatment. Setting: Three gastroenterology clinics in Denmark. Patients: Forty-two patients with histologically confirmed collagenous colitis and diarrhoea (more than three stools/day). Interventions: Patients in clinical remission after 6 weeks' open-label therapy with oral budesonide (Entocort CIR capsules, 9 mg/day) received 24 weeks' double-blind maintenance therapy with budesonide 6 mg/day or placebo. Thereafter, patients entered the 24-week, blinded follow-up period. Main Outcome Measure: The proportion of patients in clinical remission (three or fewer stools/day) at the end of maintenance therapy. Findings: A total of 34 patients in remission at week 6 were randomly assigned to budesonide 6 mg/day (n  =  17) or placebo (n  =  17). After 24 weeks' maintenance treatment, the proportions of patients in clinical remission were 76.5% (13 of 17) with budesonide and 12% (2 of 17) with placebo (p<0.001). At 48 weeks (the end of the follow-up period, without any treatment) these values were 23.5% (4 of 17) and 12% (2 of 17), respectively (p = 0.6). The median times to relapse after stopping active treatment (6 plus 24 weeks in the budesonide group; 6 weeks in the placebo group) were 39 and 38 days, respectively. Long-term treatment with budesonide was well tolerated. Conclusions: Long-term maintenance therapy with oral budesonide is efficacious and well tolerated for preventing relapse in patients with collagenous colitis. The risk of relapse after 24 weeks' maintenance treatment is similar to that observed after 6 weeks' induction therapy.